Evaluation of NovoRapid infusion as a treatment option in the management of diabetic ketoacidosis. Issue 11 (5th November 2017) - Kwok, Raylene; Sztal‐Mazer, Shoshana; Hopkins, Ria E.; Poole, Susan G.; Grannell, Louise; Coutsouvelis, John; Topliss, Duncan J.
Abstract: This study evaluates the clinical efficacy and safety of NovoRapid (insulin aspart) compared to Actrapid™ (human neutral insulin) for diabetic ketoacidosis (DKA). In this retrospective study involving 40 patients, no statistically significant differences were observed between biochemical variables, infusion duration or complications in patients treated with insulin aspart or human neutral insulin. These results support the use of insulin aspart as an effective and safe alternative to human neutral insulin in DKA.